South Africa: KwaZulu-Natal Income Dynamics Study (KIDS), 1993-1999 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
This dataset combines the KwaZulu-Natal portion of the first South African national household survey, the Project for Statistics on Living Standards and Development (PSLSD), which was undertaken in the last half of 1993 under the leadership of the Southern Africa Labour and Development Research Unit at the University of Cape Town with a re-survey of the same households from March to June 1998. Combining these two surveys yields a panel dataset in which the same individuals and households have been interviewed at two points in time. In 1993, the KwaZulu-Natal portion of the PSLSD sample was representative at the provincial level, conditional on the accuracy of the 1991 census and other information used for the sampling frame, and contained 1519 households of all races. It was decided not to re-survey the small number of white (112) and coloured (53) households in 1998. So the 1998 sample includes only African and Indian households. The 1993 survey was an integrated household survey similar in design to a World Bank Living Standards Measurement Survey. The main component was a comprehensive household survey that collected a broad array of information on the socio-economic condition of households and included sections on household demographics, household environment, education, food and non-food expenditures, remittances, employment and income, agricultural activities, health, and anthropometry. The 1998 household questionnaire largely followed the 1993 version with a few important changes: (1) greater focus on individual ownership of assets and control over their use; (2) expanded emphasis on those individuals not living in the household but economically linked to it; (3) four new sections on economic shocks, social capital, assets brought to marriage, and household decisionmaking. Community surveys were also completed in both years; the 1998 community questionnaire included new sections on economic shocks and social capital in addition to sections on local economic activity, infrastructure, and prices. This dataset, along with the Bangladesh Commercial Vegetable and Fish Polyculture Production dataset and the Strengthening and Evaluation of the Hogares Comunitarios Program in Guatemala City dataset, were collected with the objective of examining to what extent intrahousehold allocation processes would affect the outcome of development policies, with particular emphasis on gender as a determinant of intrahousehold allocation. Because the data were designed to make some analyses comparable across countries, several modules are similar for all three datasets. The common modules include: information on assets at marriage of husband and wife, family background information, individual education and anthropometric data. Other modules are different because each country study has a different emphasis. See Table 1 (PDF 65K) for a comparison of these datasets.